Pelatihan Pendampingan Pembuatan Laporan Keuangan dan Penyusunan Sistem Akuntansi Pada UMKM di Pekalongan: Khoirul Fatah*1, Usamah Bin Said2. 1,2Affiliation; 1,2 Program Studi Akuntansi, Fakultas Ekonomika dan Bisnis, Universitas Muhammadiyah Pekajangan Pekalongan - Fatah, Khoirul Fatah (Universitas Muhammadiyah Malang, 2023)
This service aims to help partners to have a reliable accounting information system that can provide important information accurately and on time. SMEs want to have a good accounting information system. Therefore, they need internal (company) and external (banks and Tax Office) roles. This hope cannot be realized because SMEs face several obstacles. The obstacle is that the company does not have human resources who have an accounting education background, minimal facilities and infrastructure (hardware and software), and limited capital. SMEs have difficulty determining how much tax to pay. This service is carried out with several kinds of activities. First; share with SME business owners to analyze transactions. Second; prepare accounting software in accordance with the information needs of SMEs (based on SAK EMKM), namely SiAPIK. Third; provide the necessary facilities and infrastructure. Fourth; conduct internal training for employees who handle bookkeeping and accounting. Fifth; accounting software implementation assistance with SiAPIK.